EXAMINING THE SAFETY IMPACTS OF TRANSIT PRIORITY SIGNAL SYSTEMS USING SIMULATION TECHNIQUES - Erdem (Scientific Journal of Silesian University of Technology. Series Transport)
Transit Priority Signal (TPS) systems are increasingly used to improve traffic efficiency and reduce passenger waiting times. However, such systems may carry potential safety risks. This study aims to investigate the safety effects of TPS at intersections. Our study utilized the SUMO traffic simulation program to create a road network model containing nine signalized intersections. Subsequently, the TPS system was applied to selected bus routes within the road network, and the cases with and without TPS implementation were compared in terms of safety and performance. In safety-oriented comparisons, surrogate safety measures were employed, including number of conflict and Time to Collision (TTC). Signalized intersection performances were measured and compared in terms of the number and duration of stops. The analysis results indicate that TPS enhances safety and transportation performance for buses, but adversely impacts safety and transportation performance for passenger cars. This study underscores the importance of considering safety aspects in the implementation of TPS aimed at improving passenger transportation efficiency. These findings may contribute to the enhancement of public transportation infrastructure and the implementation of appropriate safety measures.